Game Edukasi Pengenalan dan Pembelajaran Berhitung untuk Siswa Kelas 1 Sekolah Dasar - Yogiek Indra Kurniawan; Muhammad Fikri Rivaldi (Jurnal Manajemen Informatika (JAMIKA), 2021)
Mathematics, especially arithmetic theory, is a difficult subject for most students. Apart from the theory that is difficult to understand, students also have shortcomings in the interest in learning materials and limitations in learning media to teach arithmetic theory in mathematics. The purpose of this research is to produce an educational game as an alternative to studying arithmetic material in mathematics. The target users of this educational game are grade 1 elementary school students. This game has several features, such as displaying material in the form of images and videos in the form of learning to count from numbers 1 to 10, and counting games with drag and drop. The method used to develop this application starts from design and planning, then continues with the material collection, implementation, testing and evaluation, and application maintenance. Based on black-box testing, the results show that the educational game has been made as expected, while based on the User Acceptance Test, the results of user perceptions of the game are 94.25% with an indicator of the "Very Good" category which indicates that this educational game can be used as alternative in learning arithmetic theory in mathematics.